2017
DOI: 10.1038/srep39612
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of titanium implants entrains inflammation-induced osteolysis

Abstract: With millions of new dental and orthopedic implants inserted annually, periprosthetic osteolysis becomes a major concern. In dentistry, peri-implantitis management includes cleaning using ultrasonic scaling. We examined whether ultrasonic scaling releases titanium particles and induces inflammation and osteolysis. Titanium discs with machined, sandblasted/acid-etched and sandblasted surfaces were subjected to ultrasonic scaling and we physically and chemically characterized the released particles. These partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 25 publications
(36 reference statements)
4
103
1
3
Order By: Relevance
“…In a similar manner, bleeding on probing may only reflect low-grade chronic inflammation and/or release of titanium particles around oral implants instead of being indicative of particular forms of disease. Released titanium particles may act as additional foreign bodies initiating the release of inflammatory mediators associated with bone resorption [70][71][72][73][74][75][76][77][78] as already described in the case of orthopedic implants. 79 Evaluated sites presented a higher number of titanium particles compared to healthy implants.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%
“…In a similar manner, bleeding on probing may only reflect low-grade chronic inflammation and/or release of titanium particles around oral implants instead of being indicative of particular forms of disease. Released titanium particles may act as additional foreign bodies initiating the release of inflammatory mediators associated with bone resorption [70][71][72][73][74][75][76][77][78] as already described in the case of orthopedic implants. 79 Evaluated sites presented a higher number of titanium particles compared to healthy implants.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%
“…7,8 Leftover titanium fragments released from dental implants after the use of an ultrasonic instrument have been shown to introduce foreign bodies to the peri-implant space, which may aggravate the situation. 9 To easily access affected areas when treating dental implants, both overly contoured and rigid devices do not provide the simple access offered by a brush with a flexible shaft. The natural polysaccharide chitosan (poly-N-acetyl glycosaminoglycan) was chosen because it is a nontoxic and bioabsorbable substance that exhibits bacteriostatic and anti-inflammatory properties.…”
mentioning
confidence: 99%
“…These findings have been confirmed by Wachi et al who also found that Ti ions induced monocyte infiltration and osteoclast differentiation in the epithelium 37. Recruited macrophages will phagocytize nanoparticles of Ti‐protein aggregates into the phagolysosomes and try to degrade them 38, 39. High Ti content in the phagocytosed particles will protect them from proteolysis and result in intracellular disruption of the lysosome membrane.…”
Section: Introductionmentioning
confidence: 55%
“…37 Recruited macrophages will phagocytize nanoparticles of Tiprotein aggregates into the phagolysosomes and try to degrade them. 38,39 High Ti content in the phagocytosed particles will protect them from proteolysis and result in intracellular disruption of the lysosome membrane. This will induce the assembly of the inflammasome complex, which will activate and release pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%